Anxiety Reviewed from the Perspective of Emotional Regulation in Students Writing Their Theses - Sipayung, Apriana Evita Pricilya; Sinaga, Enzelin Yulia Betrik; Sinuhaji, Edward Aginta; Mirza, Rina; Putra, Achmad Irvan Dwi (Psyche 165 Journal, 2025)
A thesis is a final assignment that must be written by students to complete their study program. In writing a thesis, many students experience anxiety, both during guidance and when faced with the repeated revision process. Excessive anxiety can prevent students from completing their thesis on time. One factor that causes anxiety is students' emotional regulation. With good emotional regulation, students can overcome their anxiety appropriately. The purpose of this study was to assess the relationship between anxiety and emotional regulation in students who are writing a thesis. The hypothesis is "there is a negative relationship between emotional regulation and anxiety in students of the Faculty of Medicine, Islamic University of North Sumatra who are writing a thesis." The subjects of this study were 93 individual students who were writing a thesis at the Faculty of Medicine, Islamic University of North Sumatra, using a total sampling technique . The method used in this study was a quantitative method, data were collected using an emotional regulation and anxiety scale. The calculation applies the analysis prerequisite test, which includes the normality test and linearity test, as well as data analysis using Spearman correlation through the IBM SPSS Statistics 25 application , obtaining data analysis results showing a correlation coefficient value of r = -0.502 with p = 0.000 (p <0.05), which means that the higher the student's regulatory ability, the lower the level of anxiety experienced by the student, and vice versa, the lower the student's emotional regulation ability, the higher the level of anxiety experienced by the student.